Comparative analysis of the postadmission and antemortem oropharyngeal and rectal swab microbiota of ICU patients - Petrilla, Annamaria; Nemeth, Peter; Fauszt, Peter; Szilagyi-Racz, Anna; Mikolas, Maja; Szilagyi-Tolnai, Emese; David, Peter; Stagel, Aniko; Gal, Ferenc; Gal, Kristof; Sohajda, Reka; Pham, Trinh; et al. (Springer Nature, 2026)
Shotgun metabarcoding was conducted to examine the microbiota in a total of 48 samples from 12 critically ill patients, analyzing samples from both the oropharynx and rectum. We aimed to compare their postadmission microbiota, characterized as moderately dysbiotic, with the severely dysbiotic antemortem microbiota associated with patients' deaths. We found that, compared with postadmission samples, patient antemortem swab samples presented moderate but not significantly decreased diversity indices. The antemortem oropharyngeal samples presented an increase in biofilm-forming bacteria, including Streptococcus oralis, methicillin-resistant Staphylococcus aureus (MRSA), and Enterococcus faecalis. Although the septic shock rate was 67%, no significant differences were detected in the potential pathogen ratios when the microbiota was analyzed. A notable strain-sharing rate between the oropharynx and intestine was noted. By comparing postadmission and antemortem samples, microbial biomarkers of severe dysbiosis were pinpointed through the analysis of differentially abundant and uniquely emerging species in both oropharyngeal and rectal swabs. Demonstrating strong interconnectivity along the oral-intestinal axis, these biomarkers could serve as indicators of the progression of dysbiosis. Furthermore, the microbial networks of the oropharyngeal microbiota in deceased patients presented the lowest modularity, suggesting a vulnerable community structure. Our data also highlight the critical importance of introducing treatments aimed at enhancing the resilience of the oral cavity microbiome, thereby contributing to better patient outcomes.